2016
DOI: 10.1371/journal.pone.0153720
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of Association of Variants at 11q23.3 Chromosomal Region with Coronary Artery Disease and Dyslipidemia in the Population of Andhra Pradesh, India

Abstract: In our attempt to comprehensively understand the nature of association of variants at 11q23.3 apolipoprotein gene cluster region, we genotyped a prioritized set of 96 informative SNPs using Fluidigm customized SNP genotyping platform in a sample of 508 coronary artery disease (CAD) cases and 516 controls. We found 12 SNPs as significantly associated with CAD at P <0.05, albeit only four (rs2849165, rs17440396, rs6589566 and rs633389) of these remained significant after Benjamin Hochberg correction. Of the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Interestingly, the SNP included from 9p21.3 region in all the three combinations was found to be rs7865618. None of these three SNPs at 11q23.3 locus showed significant allelic association with CAD in the earlier study, except for the protective effect of rs2849165 11 . Nevertheless, in the pair wise SNP interaction analysis, all the three were shown to be contributing significantly to CAD risk in conjunction with rs7865618 from the 9p21.3 region.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…Interestingly, the SNP included from 9p21.3 region in all the three combinations was found to be rs7865618. None of these three SNPs at 11q23.3 locus showed significant allelic association with CAD in the earlier study, except for the protective effect of rs2849165 11 . Nevertheless, in the pair wise SNP interaction analysis, all the three were shown to be contributing significantly to CAD risk in conjunction with rs7865618 from the 9p21.3 region.…”
Section: Resultsmentioning
confidence: 60%
“…However, the protective effect of the SNP in interaction with other SNPs of the same 9p21.3 region indicated that it may contribute to CAD risk through its interactions with variants at other loci. Given the significant effect of variants in 11q23.3 region on CAD pathology, we made an attempt to explore the nature of pair wise interactions between the 35 SNPs of 9p21.3 and 95 SNPs of 11q23.3, analysed by us in the previous study 11 , 12 . The results revealed three significant SNP-SNP combinations between these two chromosomal loci (Table 6 ), each pair represented one SNP from 11q23.3 locus (rs2187126 in the intron of BUD13, rs1263163 and rs2849165 both in the intergenic region of APOA5-APOA4 genes).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations